fficacy of Dry Needling in Disability, Pressure Pain Threshold and Mobility in Shoulder Myofascial Pain Syndrome in Patients with Spinal Cord Injury: Pilot Study, Randomized Controlled Clinical Trial (European Journal of Health Research, 2020)
Shoulder pain in patients with spinal cord injury is one of the most prevalent pathologies, especially due to the use of assistive devices, since the joint is initially prepared for other functions. It is a hypermobile joint with little stability, so it is often injured. The aim of this study is to prove if dry needling used in these patients is effective in the disability (DASH) of the sample. In this randomized, single-blind, controlled trial, it was used the fast-in and fast-out Hong technique on an active trigger point in infraspinatus muscle within the experimental group and compared with a control group that received a treatment of placebo needle. The variables used in this study are: DASHe (Disabilities of the Arm, Shoulder and Hand version Spanish version), McGill pain questionnaire, SPADIe (Shoulder Pain and Disability Index Spanish version) that were evaluated before and one week after the intervention, and pain pressure threshold (PPT) and range of motion (ROM) of the shoulder of internal rotation and horizontal adduction that were evaluated before, immediately after and a week after the intervention. Statistical analysis was carried out using the SPSS 22.0 program, from which, after the homogeneity of the sample, there were no significant differences in any of the variables, except for the pressure pain threshold after one week between the study groups. Dry needling used in myofascial shoulder pain syndrome in patients with spinal cord injury seems effective in increasing the PPT after one week of treatment. A study with sample expansion is needed to determine the effectiveness of the intervention.